2021
DOI: 10.30831/akukeg.856221
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Analysis of the Role of Knowledge Management in Knowledge Leadership

Abstract: Knowledge-based organizational structures need leaders who manage and ensure the effectiveness of knowledge. Knowledge leaders encourage employees to participate in knowledge management processes, contribute to adopting knowledge management as part of organizational culture, and lead knowledge management activities by choosing the most appropriate infrastructure and technology. Schools are knowledge-intensive organizations that possess a large number of information areas that must be managed. The main actors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…HODs must ensure that the teachers receive the circulars (H6@C). This statement demonstrates that the leadership of the school understands the importance of encouraging all members of staff to play an active role in knowledge sharing events (Kazak, 2021). Syndicated meetings and spontaneous briefings appeared to be the most viable methods of cascading or sharing knowledge with co-workers who did not occupy management positions.…”
Section: D)mentioning
confidence: 88%
See 1 more Smart Citation
“…HODs must ensure that the teachers receive the circulars (H6@C). This statement demonstrates that the leadership of the school understands the importance of encouraging all members of staff to play an active role in knowledge sharing events (Kazak, 2021). Syndicated meetings and spontaneous briefings appeared to be the most viable methods of cascading or sharing knowledge with co-workers who did not occupy management positions.…”
Section: D)mentioning
confidence: 88%
“…It is a challenge to get everyone's buy-in on certain processes and procedures, the management is at times, resistant to change and tends to be loyal to their old ways, especially the knowledge that comes from new/younger teachers. Leader's failure to motivate, reward and recognise workers ' [i.e., teachers] knowledge sharing efforts (Šajeva, 2014) exposes their lack of knowledge leadership skills (Kazak, 2021;Nkambule, 2023b).…”
Section: C)mentioning
confidence: 99%
“…Swanepoel ( 2008) points out that the role of principals has gone through significant changes in the last few years. The promise of 21 st first century education has diversified their leadership functions to include knowledge management leadership (Kazak, 2021) which, inter alia, deals with overseeing the implementation of SA-SAMS. In addition to complex leadership functions, their administrative workload has also drastically increased (Swanepoel, 2008).…”
Section: Principals' Association With Sa-samsmentioning
confidence: 99%
“…This is a far cry from a few years prior, when they carried out minimal data management tasks and were not expected to operate a computer. To lessen the tediousness of "management and administration of the school" (Kuraikose, 2014, p. 77), SA-SAMS was created as an allencompassing digital platform for them to perform all areas of their job description (Department of Basic Education [DBE], 2012) and enhance their knowledge management leadership capabilities (Kazak, 2021;Nkambule, 2023d). Based on their interpretation of related research, Kasimiri et al (2021) concluded that the introduction of SMSs professionalised principalship by ensuring that individuals entrusted with it acquired ICT skills and developed effective administration competencies.…”
Section: Principals' Association With Sa-samsmentioning
confidence: 99%
See 1 more Smart Citation